THE EFFECT OF CUSTOMER EXPERIENCE, CUSTOMER EXPECTATIONS, AND CUSTOMER SATISFACTION TO CUSTOMER LOYALTY AT ROBUSTO COFFEE MALANG - Wijaya, Hans Chandra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
This research aimed to test and analyze the effects of customer experience, customer expectations, and customer satisfaction on Robusto Coffee customer loyalty. The research type used is descriptive research. The research was conducted at Robusto Coffee. The research period was conducted with cross sectional data by the observation time of approximately 7-14 days. The types of data used are primary and secondary data. The sampling technique used was nonprobability sampling. In this research, the researchers used regression analysis, and then analyzed the data using excel tools and SPSS 20. Based on the research results, it can be concluded that customer experience, customer expectations, and customer satisfaction have a positive and significant effect on customer loyalty at Robusto Coffee Malang. Practically the findings of this study have implications for business strategy and marketing management at Robusto Coffee Malang.Keywords: Customer Experience, Customer Expectations, Customer Satisfaction, Customer Loyalty